On the Decay Property of Solutions of Viscous Burgers Equation with Boundary Feedback (Journal of Partial Differential Equations, 2010)
In this article, we will investigate the viscous Burgers equation with boundary feedback. The existence of the solution is proved by constructing a convergence sequence inductively. Moreover, the decay property of the solution is shown based on the maximum principle for nonlinear parabolic equations.
Keywords: Burgers equation; nonlocal boundary; maximum principle